Kajian Manfaat Senyawa Aktif dalam Ekstrak Kulit Buah Coklat (Theobroma Cacao ) - Sukatik - -; Yuli Yetri -; Rahmi Hidayati -; Roni Tri Putra; Ratih Paramitha - (Jurnal Ilmiah Poli Rekayasa, 2020)
Identification of active compounds in cacao pod rind has been done. Cacao pod rind contained active compound alkaloid, theobromine (3,7-dimethylxanthine). Cacao pod rind extract contained some other active compounds mixed flavonoid or condensed tannin such as anthocyanin, anthocyanidin, catechin, epicatechin, epigallocatechin, and leucoanthocyanidin. Cacao pod rind was extracted by maceration using methanol 70% and fractionated with hexane and ethyl acetate to obtain polar extracts. This study used an experimental method that was analyzed descriptively using Gas Chromatography-Mass Spectrometry (GC-MS) and Liquid Chromatography-Mass Spectrometry (LC-MS). Phytochemical screening test showed cocoa pod rind extracts contained alkaloids, flavonoids, tannins, terpenoids, and saponins. GC-MS analysis showed that cacao pod rind extracts contained 24 compounds. Polar extracts analysis with LC-MS obtained 10 compounds contained hydroxy groups, which can be used as corrosion inhibitors on metal. The result of this study showed that cocoa pod rind has potential as corrosion inhibitor. It also has potential as an anti-bacterial and antioxidant.